Feasibility of total laparoscopic hysterectomy as a day care procedure - Thyagaraju, Chitra; Modi, Rajesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Aim of current study was to evaluate the feasibility of Total Laparoscopic Hysterectomy (TLH) as a day care procedure and compare its outcome in relation to uterine size. Methods: A retrospective cohort study of all patients who underwent total laparoscopic hysterectomy for benign pathologies between March 2010 to April 2011 at Akola endoscopy centre, Akola, Maharashtra, were included in the study. Demographic and surgical data like estimated blood loss, operating time, rate of complications were analysed. Re-admission and re-operation rate were also analysed. A comparison between uterine height <12 weeks and uterine height >12 weeks were performed. Analysis was performed by SPSS version 15 and chi-square test. Results: The mean age of the patients was 43.05 years (range 32-66 years). The mean parity was 2.1 (range 1-4). The mean operating time was 52.83 minutes (range 40- 115), which varied according to the uterine sizes, with a mean 52.4 (range 40-68) for smaller uterus <12 weeks and for a uterus >12 weeks mean operative time was 68.23 (range 55-115 minutes) which was statistically significant (P = 0.000). The mean estimated blood loss was significantly less in patients with small uteri at 40.20 ml (range 15-80) than in patients with uterus >12 weeks, at 62.50 ml (range 40-250). (P = 0.001). There were no major intraoperative/post-operative complications. Minor post-operative complication rate was 7%. The Mean hospital stay was 8.2 hours (5 hours - 12 hours).The re-admission rate was 4%. Conclusions: These preliminary data suggests that day care laparoscopic hysterectomy is feasible, safe with greater efficacy; however the skill of the surgeon matters. With better understanding of the technique, the advent of better anaesthetic agent, increased surgical experience and patient awareness has helped Day care surgery in to an art and which can be considered as a speciality.